2015
DOI: 10.1007/s40279-015-0364-1
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Pain in Adolescence and Adulthood: Same Same, but Different?

Abstract: The mainstay of patellofemoral pain (PFP) treatment is exercise therapy, often in combination with adjunct treatments such as patient education, orthoses, patella taping and stretching, making the intervention multimodal in nature. The vast majority of randomised controlled trials among patients with PFP have investigated the effect of treatment among adults (>18 years of age). So, while systematic reviews and meta-analyses provide evidence-based recommendations for treating PFP, these recommendations are larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 59 publications
3
79
2
2
Order By: Relevance
“…In contrast to our findings, Rathleff et al 13 showed that the success rate of treatment differed between adult and adolescent patients with PFP who performed similar exercises and had comparable compliance. Others have also reported lower success rates (29%-53%) in adolescent patients with PFP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Rathleff et al 13 showed that the success rate of treatment differed between adult and adolescent patients with PFP who performed similar exercises and had comparable compliance. Others have also reported lower success rates (29%-53%) in adolescent patients with PFP.…”
Section: Discussioncontrasting
confidence: 99%
“…13 As a consequence, the importance of getting a better understanding of the pathology and prognosis in both adolescents and adults was emphasized. The present study investigated potential differences in patient characteristics, reported symptoms, and reported pain and function at 1-year follow-up between adolescents and adults with PFP.…”
mentioning
confidence: 99%
“…Embora a prevalência da DFP seja maior em mulheres e em adolescentes do sexo feminino [10,23], o presente estudo mostra que adolescentes do sexo masculino com DFP possuíam maiores níveis de dor autorreportada. Isso pode indicar que, embora as adolescentes do sexo feminino sejam mais acometidas pela DFP, os adolescentes do sexo masculino apresentam maior severidade dos sintomas.…”
Section: Discussionunclassified
“…De acordo com Rathleff et al [10], mais de 1500 artigos científicos já foram publicados na área da DFP nos últimos 30 anos e menos de 5% desses estudos envolvem adolescentes. Na maioria dos casos, adolescentes com DFP apresentam sintomatologia de mais de três anos [11], e apenas 5% reportam duração da dor por menos de seis meses [12].…”
Section: Introductionunclassified
“…Idiopathic anterior knee pain, also described as patellofemoral pain syndrome, refers to non-specific, vague, mostly activity related anterior knee pain and is the most common cause of knee pain in adolescents (8)(9)(10)(11)(12). Gorman McNerney and Arendt state that idiopathic anterior knee pain affects around 30% of the adolescent population (13).…”
Section: Idiopathic Anterior Knee Painmentioning
confidence: 99%